Corticospinal tract sprouting in the injured rat spinal cord stimulated by Schwann cell preconditioning of the motor cortex. (1st September 2013) - Wills, Taryn E; Batchelor, Peter E; Kerr, Nicole F; Sidon, Kate; Katz, Melissa; Loy, Candace; Howells, David W
<x xml:space="preserve">Abstract</x> Peripheral nerve preconditioning lesions have been shown to consistently enhance sensory nerve regeneration in the injured spinal cord. Objective: The aim of this study was to determine if the rat motor cortex could be preconditioned through the implantation of Schwann cells (SC), thereby stimulating sprouting and regeneration of the corticospinal tract (CST). Methods: Schwann cells (cultured in vitro) were injected into the motor cortex and seven days post-surgery rats underwent a dorsal spinal hemisection injury. Eight weeks following spinal injury animals were perfused and the CST visualised by Avidin-peroxidase histochemistry for dextran-biotin. Results: Results demonstrate substantially enhanced CST collateral sprouting in both the rostral grey and white matter of the injured spinal cord in animals with SC implanted into the motor cortex compared to control animals with and without cortical vehicle injections. Corticospinal tract peri-wound regenerative sprouting was also enhanced in animals implanted with cortical SC compared to controls, however, only a small degree of CST axonal regeneration was present in the grey matter beneath the injury site. In all groups, CST peri-lesional regenerative sprouting occurred in close proximity to macrophages. Complicated and intimate relationships between CST fibres and these cells were evident. Discussion: Overall, our data demonstrates that preconditioning the motor cortex with SC prior to spinal injury results in greatly enhanced CST sprouting and that CST peri-wound sprouting takes place in juxtaposition to macrophages.